2017
DOI: 10.1371/journal.pone.0182167
|View full text |Cite
|
Sign up to set email alerts
|

Contamination with HIV antibody may be responsible for false positive results in specimens tested on automated platforms running HIV 4th generation assays in a region of high HIV prevalence

Abstract: IntroductionIn South Africa where the prevalence of HIV infection is very high, 4th generation HIV antibody/p24 antigen combo immunoassays are the tests of choice for laboratory based screening. Testing is usually performed in clinical pathology laboratories on automated analysers. To investigate the cause of false positive results on 4th generation HIV testing platforms in public sector laboratories, the performance of two automated platforms was compared in a clinical pathology setting, firstly on routine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…FP results usually generate LP&E S/CO signals as seen by other centres [ 2 , 6 , 7 ]. Using a combination of independent sample testing and different platform testing, for confirmation, we found that 85% of LP&E results were FP and therefore, LP&E result prevalence can be used as an indicator of FP rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FP results usually generate LP&E S/CO signals as seen by other centres [ 2 , 6 , 7 ]. Using a combination of independent sample testing and different platform testing, for confirmation, we found that 85% of LP&E results were FP and therefore, LP&E result prevalence can be used as an indicator of FP rate.…”
Section: Discussionmentioning
confidence: 99%
“…In a high prevalence setting, prior research by Hardie et al (2017) found that repeatedly processing known HIV negative samples through automated platforms increased the probability of the sample subsequently testing positive [ 2 ]. A similar platform and setting exist at TBH NHLS where the Roche® Modular Pre-Analytic System (MPA) is used to process samples received for Clinical Chemistry, Immunology and Virology.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential consequences of false-positive or discordant results on blood shortage and clinical management of donors since a misdiagnosis may lead to inappropriate treatments, measures should be taken to avoid or at least limit them [30,31]. Alongside well-performed laboratory testing, implementing an efficient quality system that includes organizational management, quality standards, traceability, equipment qualification, reagent verification before use, regular staff training and participation to proficiency studies may improve the performance of the screening test.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth generation HIV laboratory based tests are more sensitive than third generation rapid tests, but have other problems such as increased turnaround time (resulting in possible delays in treatment and loss to follow up) and particular automated assays may be prone to sample contamination. 28 Most fourth generation HIV serology platforms are also not validated for testing with DBS, but some studies have shown promise. 31 Given that the DBS technique is currently the only means of sample transport over long distances and without the need for cold storage, it will be important for manufacturers of laboratory-based tests to validate their platforms for use with DBS.…”
Section: Discussionmentioning
confidence: 99%